Implementing sanitation marketing as a form of social marketing: A case scheduled desludging service, Malang City - Ari Kuswandari Yushinta; Martaleni Martaleni; Rini Astuti (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2022)
To reach sustainable development goal 6, “clean water and sanitation,” the government has made it mandatory to implement the Scheduled Desludging Service program (in the Indonesian language as layanan lumpur tinja terjadwal / L2T2). The L2T2 program is a septic tank desludging service in a given desludging period following a set desludging schedule. Malang City has successfully implemented the program within a short period despite starting the program only recently, in 2019. The researchers employed a qualitative research design with the case study method to derive a meaning behind a phenomenon, given that the program is actual, specific, and detailed. The research results indicated that the L2T2 program implementation in Malang City had met 7 of 8 criteria under the L2T2 program guideline set by the Ministry of Public Works and Housing. The one criterion that needed to be fulfilled concerning service pricing. Instead, the sanitation marketing implementation in the L2T2 program has met 7 of 10 standards in the sanitation marketing aspect—the three criteria needed to be fulfilled service pricing, CSR strategy, and loyalty program.